Pembinaan Aksara Bali Dan Dharmagita Pada Masyarakat Hindu Di Banjar Purwa Karya Lombok Timur - Wirawan, I Wayan Ardhi; Anom, Anak Agung Istri; Sumada, I Ketut; Kembarawan, I Gusti Komang; Sari, Ni Kadek Mira Widya (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2023)
This article aims to explain the activities of developing Balinese script and dharmagita in pockets of Hindus who live in the Purwa Karya Hamlet area, Pandak Guar Village, East Lombok. This phenomenon relates to a pilot program to instill religious cultural values in communities in Hindu enclaves. There are two methods used in coaching activities, namely the lecture method and the practical method. The lecture method is prioritized to provide an understanding of aspects related to Hindu teachings and their implementation in everyday life. The practical method is applied in training participants to be able to master the material presented. The results of coaching activities as output for coaching Balinese script and dharmagita are categorized into two. First, the development of Balinese script through guidance methods is oriented towards understanding Balinese script as a tool for reading lontar manuscripts using Balinese. The practical method is weighted on writing skills and reading Balinese script. Second, dharmagita counseling is carried out through a mentoring method which is weighted on theoretical aspects in understanding teachers and songs in reading kakawin texts. The practical method emphasizes the aspect of the ability to chant the wirama and gartos of the text being read.